PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS E-LEARNING MADRSAH DALAM MATA PELAJARAN FIQIH PADA MASA PANDEMI COVID-19 DI MA ALMAARIF SINGOSARI - Lia Miftakhul Jannah; Maskuri Maskuri; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The use of Madrasah E-learning-based learning media in Fiqh subjects during the Covid-19 pandemic created a new challenge for education units, teachers and students at MA Almaarif Singosari. The focus of the research discusses the planning, implementation process, and evaluation of the use of Madrasah E-learning-based learning media in Fiqh subjects during the Covid-19 pandemic at MA Almaarif Singosari. To achieve this goal, the researcher uses a qualitative approach with the type of case study research. Researchers found research results from planning including curriculum evaluation, preparing educators, and learning implementation plans (RPP). The implementation process includes preliminary activities, core activities using a scientific approach, and closing activities. Evaluation includes evaluation of cognitive aspects, evaluation of affective aspects, and evaluation of psychomotor aspects.